VistronAI: Unlocking the Future of AI-Powered Multimedia Interaction - Sonali Bhanudas Mali; Akanksha Ramesh Solankurkar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The integration of Large Language Models (LLMs) into various applications occurs because of increasing demands for intelligent automation and real-time decision-making. LLMs power extensive business potential which enables operational improvements along with workflow streamlining and productivity improvements for various industries. VistronAI aims to develop a suite of six LLM-based applications designed to tackle challenges in areas such as data analysis, content generation, and automation. VistronAI addresses these challenges by integrating applications for audio, video, document, URL analysis, OCR for images, and real-time Q&A. By using advanced LLM technologies, the suite combines natural language processing and machine learning techniques to solve complex real-world problems. The combination of improved information retrieval with workflow automation position VistronAI as a robust solution for AI-driven content analysis, multi-modal data processing across diverse use cases.